Kinerja Keuangan Terhadap Nilai Perusahaan: Peran GIC dan CSR Sebagai Pemoderasi - Maelly Widiana Putri; Achmad Murdiono (AFRE (Accounting and Financial Review), 2022)
The purpose of this study was to examine the effect of financial performance on firm value moderated by green intellectual capital (GIC) and corporate social responsibility (CSR). This study uses mining companies listed on the Indonesia Stock Exchange (IDX). The side technique used is purposive sampling. The data used is secondary data in the form of company annual reports for 2017-2020. The data analysis technique was carried out using the partial least square method. The results showed that financial performance affects firm value. However, green intellectual capital cannot moderate the relationship between financial performance and firm value. Meanwhile, corporate social responsibility can strongly moderate the relationship between financial performance and firm value. DOI: https://doi.org/10.26905/afr.v5i3.7899Â